Toxic dinoflagellates and Vibrio spp. act independently in bivalve larvae. (October 2016) - De Rijcke, M.; Van Acker, E.; Nevejan, N.; De Schamphelaere, K.A.C.; Janssen, C.R.
Abstract: Harmful algal blooms (HABs) and marine pathogens – like Vibrio spp. – are increasingly common due to climate change. These stressors affect the growth, viability and development of bivalve larvae. Little is known, however, about the potential for interactions between these two concurrent stressors. While some mixed exposures have been performed with adult bivalves, no such work has been done with larvae which are generally more sensitive. This study examines whether dinoflagellates and bacteria may interactively affect the viability and immunological resilience of blue mussel Mytilus edulis larvae. Embryos were exposed to environmentally relevant concentrations (100, 500, 2500 & 12, 500 cells ml −1 ) of a dinoflagellate ( Alexandrium minutum, Alexandrium ostenfeldii, Karenia mikimotoi, Protoceratium reticulatum, Prorocentrum cordatum, P. lima or P. micans ), a known pathogen ( Vibrio coralliilyticus/neptunius -like isolate or Vibrio splendidus ; 10 5 CFU ml −1 ), or both. After five days of exposure, significant (p < 0.05) adverse effects on larval viability and larval development were found for all dinoflagellates (except P. cordatum ) and V. splendidus . Yet, despite the individual effect of each stressor, no significant interactions were found between the pathogens and harmful algae. The larval viability and the phenoloxidase innate immune system responded independently to each stressor. This independence may be related to a differential timing of the effects of HABs and pathogens. Highlights: Blue mussel larvae were simultaneously exposed to harmful algae and pathogens. Larval viability and development were lower at naturally occurring concentrations. The phenoloxidase immune activity responded to both algae and pathogens. Main effects of each stressor appear separated in time. Toxic dinoflagellates do not change the susceptibility of larvae towards Vibrio spp.